2020
DOI: 10.1177/0011392120927755
|View full text |Cite
|
Sign up to set email alerts
|

Architectures of asylum: Making home in a state of permanent temporariness

Abstract: Urban research in Germany has started to address the socio-spatial distribution and architectures of so-called collective accommodation for asylum seekers, refugee camps, and new forms of ethnic segregation triggered by refugee movements in recent years. The spatial practices of refugees themselves within these processes have not yet been a subject of substantive research. Combining research methods from social and architectural sciences, this article investigates the physical, material, social and symbolic ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Refugee accommodation policies have been significantly reshaped in a series of European countries since 2015, leading to renewed academic interest in the field (Darling, 2017, 2020; El Moussawi and Schuermans, 2021; Kreichauf, 2018; Novak, 2021; Semprebon, 2021; Steigemann and Misselwitz, 2020). This article, which is part of the Special Issue ‘Urban Europe, Precarious Futures?’, brings to the forefront the case of Greece as not only one of the main entry countries but also as an important part of the wider European reception system.…”
Section: Introductionmentioning
confidence: 99%
“…Refugee accommodation policies have been significantly reshaped in a series of European countries since 2015, leading to renewed academic interest in the field (Darling, 2017, 2020; El Moussawi and Schuermans, 2021; Kreichauf, 2018; Novak, 2021; Semprebon, 2021; Steigemann and Misselwitz, 2020). This article, which is part of the Special Issue ‘Urban Europe, Precarious Futures?’, brings to the forefront the case of Greece as not only one of the main entry countries but also as an important part of the wider European reception system.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we revealed that spatial practices are also key to urbanizing refugee camps and turning them into homes (Steigemann and Misselwitz 2020;Misselwitz 2009). For instance, Romola Sanyal (2011) has explained how, despite the policing practices and attempts to maintain the temporal nature of the camp, refugees most often manage to urbanize their accommodations through the incremental practice of building under cover of their tents and bribing policemen.…”
Section: The Communicative Power Of Spatial Practices: a Theoretical ...mentioning
confidence: 97%
“…While it is less common to have large‐scale camp structures in Germany that offer shelter to thousands of refugees, scholars have pointed to the “campization” (Kreichauf, 2018) of the accommodation centres to draw attention to their isolated and permanently temporary nature. Recent scholarship on post‐2015 refugees' reception conditions through different case studies have attended to the “the situated materiality” of the reception centres, that is to say to their interaction with the surrounding infrastructure (Nettelbladt & Boano, 2019), practices of bordering and debordering that are reproduced by volunteers (Blank, 2021) as well as the resistance and home‐making of refugees (Steigemann & Misselwitz, 2020). In this special issue, comparing three accommodation centres in the same city, Seethaler‐Wari and Yanaşmayan (2023) seek to reveal intersecting forms of socio‐spatial exclusion by analysing differing internal and external spatial arrangements as well as the regulation of space and social relations between forced migrants and social workers and volunteers inside the accommodation centres.…”
Section: Accommodation and Housingmentioning
confidence: 99%